Cross‐validation of the Self‐care Ability Scale for Elderly (SASE) in a sample of Italian older adults. Issue 4 (31st May 2018) - Raffaele, Barbara; Biagioli, Valentina; Cirillo, Luciana; De Marinis, Maria Grazia; Matarese, Maria
Abstract : The assessment of self‐care among older adults is important as it permits the tailoring of educational interventions directed to prevent health deterioration and contrast the effects of ageing. The Self‐care Ability Scale for the Elderly (SASE) was developed to assess the perceived self‐care ability in older adults. Its psychometric properties were tested only in Scandinavian countries and China. This research was a cross‐validation of the SASE on 402 Italian adults aged 65 and older recruited in hospitals, clinics and homes, from September 2016 to February 2017. We performed exploratory and confirmatory factor analyses on two subsamples and identified three factors, self‐care ability to perform ADLs, self‐care ability to achieve well‐being and self‐care ability to set personal goals, with a good model fit (CFI > 0.93; RMSEA = 0.07; SRMR = 0.06). We eliminated four items, however, to improve the structural validity. Internal consistency for the three factors of the Italian version of the SASE (SASE‐I) ranged from 0.72 to 0.92. The test–retest reliability indicated good stability of the scale (ICC coefficient = 0.92). We assessed convergent validity by comparing the SASE‐I with the Katz Index of Independence in Activities of Daily Living and the Lawton Instrumental Activities of Daily Living Scale, showing moderate‐to‐strong correlations. In addition, the SASE‐I discriminated the self‐care ability in groups with different ages, levels of education and settings. Our study produced a 13‐item version of the SASE with good psychometric properties that could be recommended for use in clinical practice and research after further validation on different populations and settings.